Connection between physical activity and level of social skills in children - Joca Zurc (Zdravniški Vestnik, 2012)
Background: Recognizing and understanding the role of physical activity in child development is necessarily in order to study the connection between children’s developmental characteristics and physical activity. This has been well documented in previous research for physical development; however, little is known about the role of physical activity in children’s social development. The aim of this research was to study the connection between the level of children’s social skills and physical activity. Methods: An empirical study based on quantitative research design was undertaken. A total of 1,782 children (mean age 10.4) were selected with multilevel random sampling from a population of students attending the second educational cycle of Slovene primary schools. Physical activity was examined using a structured questionnaire, and the level of social skills was assessed using the Social Skills Rating System. The data were analyzed in SPSS 20.0 with multiple regression analysis. Results: Non-organized physical activity with friends and when home alone was most frequent in the studied sample. A third of children were active in organized physical activities with a mean duration of 2.5 years. Watching television was the most frequent sedentary pursuit. In social skills, expected maturity level was the most common predictor (60.8 %), with female students significantly outperforming their male counterparts (p < 0.001). Multiple regression analysis results revealed that physical activity has a significant influence on children’s level of social skills (F = 14.056, p < 0.001) and explained 24 % of variance. Social skill development is significantly higher among female students compared to male students (β = -0.256, p < 0.001), and increases with the duration of organized physical activity involvement (β = 0.173, p < 0.001), the frequency of physical activity in the family (β = 0.160, p < 0.001), and with the frequency of physical activity in sport clubs (β = 0.126, p = 0.001). Conclusions: The results reveal a connection between physical activity and children’s level of social skills in areas such as cooperation, assertion, empathy and self-control. Research results provide the starting point for creating physical activity programs, which will promote child development.